Penyuluhan Deteksi Dini dan Penanganan Awal Kegawatdaruratan pada Anggota Perhimpunan Mahasiswa Indonesia di Thailand (Permitha) Simpul Khon Kaen - Purwanti, indri astuti; Muryadi, Elvaro Islami; Rokhani (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
The Association of Indonesian Students in Thailand (Permitha) Node Khon Kaen has a health and sports division, but there are no health promotion activities. In fact, there have been 3 cases of member morbidities and they were handled incorrectly without paying attention to the urgency, severity, or emergency. Therefore, community service implementers provide health education on early detection and initial handling of emergencies. The method of this activity is pretest-posttest design with an instrument in the form of a questionnaire. The participants were selected by accidental sampling as many as 11 people. The collected data were processed and analyzed using mean, standard deviation, median, minimum value and maximum value for univariate analysis. The bivariate analysis was carried out using paired sample t-test. The results of data analysis showed that the majority of participants were non-health graduate students (54.5%) living in off-campus apartments (72.7%), and aged less than 26.5 years (63.6%). The mean knowledge score after counseling was higher than before counseling by 3.36 points (95% CI: 2.11 to 4.61; p-value < 0.001). In conclusion, the health education on early detection and early treatment of emergencies was successful in increasing participants' knowledge.